Business incubators as economic development tools: rethinking models based on the Korea experience. (23rd November 2005) - Kim, Hong; Ames, Michael
The growth rate of Korean business incubators (BI) is explosive compared to growth rate of incubation programs in the United States of America. The authors' secondary and primary research reveals that the stresses of rapid growth exposed difficulties with existing models. These difficulties can be better addressed by working models that extend existing, descriptive frameworks and models. It is hoped the working models presented in this article will aid in dealing with the challenges faced by the Korean BI industry, and will perhaps have general application to the 3, 000 plus BI in other countries.